Sequencing of Uniform Multifunctional Oligoesters via Random Chain Cleavages. (7th April 2022) - Soete, Matthieu; Du Prez, Filip E.
Abstract: Sequence‐defined polymers have been the object of many fascinating studies that focus on their implementation in both material and life science applications. In parallel, iterative synthetic methodologies have become more efficient, whereas the structure elucidation of these molecules is generally dependent on MS/MS analysis. Here, we report an alternative, simple strategy for the determination of the monomer order of uniform oligo(thioether ester)s. This approach, which relies on random cleavages of ester units within the macromolecular backbone via a basic treatment, enables the swift characterization of these macromolecules without the need for MS/MS. Consequently, this method can be used for decoding any information stored within the primary structure of oligoesters by means of ESI‐ or LC–MS. Finally, we speculate that a range of structurally diverse backbones could be susceptible towards this approach, which could promptly expand the library of chemically sequenceable macromolecules. Abstract : A strategy for the determination of the monomer order of sequence‐defined macromolecules by making use of ESI‐ or LC–MS is described. This approach, which relies on the introduction of random chain cleavages within the macromolecular backbone, enabled the rapid chemical sequencing of abiotic macromolecules.